A case of ulcerative colitis and pyostomatitis vegetans in an African. Issue 1 (January 1970) - Naish, J. M.; Batchvarov, B. D.; Lawoyin, V. L.
Abstract : A case of pyostomatitis vegetans and ulcerative colitis in a 26-year-old African is described. The colitis, confirmed clinically and radiologically, antedated the development of pyostomatitis. Systemic corticosteroids apparently cured the pyostomatitis but only caused an improvement in the ulcerative colitis. The rarity of ulcerative colitis amongst the Nigerian population and of pyostomatitis vegetans as a complication makes the occurrence of these two diseases in a Nigerian an extraordinary event.